『전경(典經)』에 나타난 치병의 유형과 치유적 함의 - 황희연; Hwang Hee-yeon (大巡思想論叢, 2024)
This article attempts to identify cases of healing described in Jeon-gyeong (The Canonical Scripture), Daesoon Jinrihoe's main scripture, by type and examine their characteristics and implications. Jeungsan compared the Former World to a diseased state such as "a boil on the body" and the point of "annihilation." By diagnosing the world as falling under the dominance of sanggeuk (mutual contention) and executing cheonji-gongsa (the Reordering works of Heaven and Earth) for 9 years, He attempted to change the order of the universe from sanggeuk (mutual contention) to sangsaeng (mutual beneficence). In order to save all the people in the world, Jeungsan tried to "resolve the grievances and grudges accumulated from time immemorial by recalibrating the Degree Number of Heaven and Earth, harmonizing divine beings, and establishing the Later World's paradisiacal land of immortals which will be based on the principle of mutual beneficence." In this context, it can be said that in Jeungsan's cheonji-gongsa, which aimed to save and restore to normalcy throughout the Three Realms of Heaven, Earth, and Humankind, there is an implied remedial meaning. If Daesoon Jinrihoe's tenets, creeds, aims, precepts, ethical rules, and other cultivation methods, can be correctly understood and practiced, then the healing process will also take place concurrently. Thus, the healing implications seen through this remedial principle can be distinguished into healing via cheonji-gongsa on cosmic level and healing through cultivatory practices on human level. In addition, the process of healing and restoration throughout the Three Realms of Heaven, Earth, and Humankind are in line with the practice to ultimately attain the religious aims of Daesoon Jinrihoe, which indicates the justification and significance of healing cultivatory practices. 본 논문은 대순진리회의 경전인 『전경』에 나타난 치병 사례들을 유형별로 분류하고, 그 특징과 치유적 함의를 체계적으로 고찰하고자 한다. 증산(甑山)은 당대의 선천 세계를 '종기를 앓음', '진멸할 지경' 등과 같이 병적인 상태로 진단하였다. 이러한 상극에 지배된 세상을 바로잡기 위해 그는 9년 동안 천지공사(天地公事)를 행함으로써 상극에서 상생으로 우주의 질서를 전환하고자 했다. 이에 따라 천지의 도수(度數)를 정리하고 신명을 조화시켜, 만고의 원한을 해원하고 상생의 도(道)로 후천의 선경을 건설하여 세계 민생을 구제하려 한 증산의 천지공사에는 천·지·인 삼계(三界)를 소생시키고 정상적으로 회복시키려는 치유적 의미가 내포되어 있다고 볼 수 있다. 따라서 현재 대순진리회의 종지·신조·목적·훈회·수칙 및 기타 수도 방법들을 올바르게 이해하고 실천한다면, 그 수도 과정에서 자연스럽게 치유의 과정이 병행되고 있음을 알 수 있다. 이처럼, 치병의 원리를 통해 살펴본 치유적 함의는 우주적 차원에서의 천지공사로서의 치유와 인간적 차원에서의 실천수행으로서의 치유로 구분될 수 있다. 더 나아가, 천·지·인 삼계의 치유 및 회복의 과정은 궁극적으로 대순진리회의 종교적 목적을 실현하기 위한 실천과 부합하며, 이는 치유적 실천수행의 당위성과 그 의의가 중요함을 시사한다.